Implementation Of Business Strategies In Facing Coffee Industry Competition (Case Study of PT. Ulubelu Cofco Abadi - Michaellim Michaellim; Habiburahman Habiburahman (Cita konsultindo, 2024)
Ulubelu Cofco Abadi is one of them business coffee home industry in Bandar Lampung. The problems faced by PT. Ulubelu Cofco Abadi , namely PT Sales . Ulubelu Cofco Perpetual fluctuates . This research aims to find out what business strategies should be used to obtain a market leader position for PT. Ulubelu Cofco Abadi. The method used in This research is a qualitative analysis method, using the SWOT analysis tool ( strength , weakness, opportunity and threat) Judging from the Cartesian SWOT diagram where PT. Ulubelu Cofco Abadi is in quadrant 1, namely: strategy cost leadership ( reducing total costs , determining the right cost price), strategy differentiation (adding new products, food or drinks), focus strategy ( maintaining product quality , cleanliness is always maintained, more friendly service to consumers ) .